Dilution effect of the building area on energy intensity in urban residential buildings - Jingxin Gao (Nature Portfolio, 2019)
Improving residential building energy consumption (RBEC) efficiency is important. The authors here test whether the measure truly reflects efficiency, and found that RBEC per square meter decreases with the increase of the building area per household, indicating the dilution effect.